Vascular Normalization: A New Window Opened for Cancer Therapies - Yang, Ting; Xiao, Hongqi; Liu, Xiaoxia; Wang, Zhihui; Zhang, Qingbai; Wei, Nianjin; Guo, Xinggang (Frontiers in Oncology, 2021)
Preclinical and clinical antiangiogenic approaches, with multiple side effects such as resistance, have not been proved to be very successful in treating tumor blood vessels which are important targets for tumor therapy. Meanwhile, restoring aberrant tumor blood vessels, known as tumor vascular normalization, has been shown not only capable of reducing tumor invasion and metastasis but also of enhancing the effectiveness of chemotherapy, radiation therapy, and immunotherapy. In addition to the introduction of such methods of promoting tumor vascular normalization such as maintaining the balance between proangiogenic and antiangiogenic factors and targeting endothelial cell metabolism, microRNAs, and the extracellular matrix, the latest molecular mechanisms and the potential connections between them were primarily explored. In particular, the immunotherapy-induced normalization of blood vessels further promotes infiltration of immune effector cells, which in turn improves immunotherapy, thus forming an enhanced loop. Thus, immunotherapy in combination with antiangiogenic agents is recommended. Finally, we introduce the imaging technologies and serum markers, which can be used to determine the window for tumor vascular normalization.